Synthesis of chitosan/hydroxyapatite membranes coated with hydroxycarbonate apatite for guided tissue regeneration purposes - Fraga, Alexandre Felix; de Almeida Filho, Edson [UNESP]; da Silva Rigo, Eliana Cristina; Boschi, Anselmo Ortega (Elsevier B.V., 2011)
Chitosan, which is a non-toxic, biodegradable and biocompatible biopolymer, has been widely researched for several applications in the field of biomaterials. Calcium phosphate ceramics stand out among the so-called bioceramics for their absence of local or systemic toxicity, their non-response to foreign bodies or inflammations, and their apparent ability to bond to the host tissue. Hydroxyapatite (HA) is one of the most important bioceramics because it is the main component of the mineral phase of bone. The aim of this work was to produce chitosan membranes coated with hydroxyapatite using the modified biomimetic method. Membranes were synthesized from a solution containing 2% of chitosan in acetic acid (weight/volume) via the solvent evaporation method. Specimens were immersed in a sodium silicate solution and then in a 1.5 SBF (simulated body fluid) solution. The crystallinity of the HA formed over the membranes was correlated to the use of the nucleation agent (the sodium silicate solution itself). Coated membranes were characterized by means of scanning electron microscopy - SEM, X-ray diffraction - XRD, and Fourier transform infrared spectroscopy - FTIR. The results indicate a homogeneous coating covering the entire surface of the membrane and the production of a semi-crystalline hydroxyapatite layer similar to the mineral phase of human bone. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Biomimetic method; Chitosan; Membranes and hydroxyapatite